Behavior of σ3 Grain Boundaries in CuInSe2 and CuGaSe2 Photovoltaic Absorbers Revealed by First-Principles Hybrid Functional Calculations - Mirhosseini, Hossein; Kiss, Janos; Felser, Claudia (Physical Review Applied, 2015)
The inconclusive results of the previous first-principles studies on the Σ3 grain boundaries (GBs) in CuInSe2 reveal the importance of employing a method that can correctly describe the electronic structure of this solar-cell material. We employ hybrid functional calculations to study the Σ3(112) and Σ3(114) GBs in CuInSe2 and CuGaSe2. The electronic structure changes introduced by the formation of GBs are threefold: the creation of gap states, a shift in band edges, and the alteration of band-gap sizes. Gap states commonly behave as recombination centers, but the band alignment and the change in the band-gap size induced by GBs mitigate the destructive effect of these states in CuInSe2. That means that Σ3 GBs are not detrimental for the carrier transport in devices based on CuInSe2. Conversely, these GBs are destructive for the carrier transport in CuGaSe2. The different behaviors of the Σ3 GBs in CISe and CGSe might be considered by experimentalists to optimize the device fabrication to achieve high-performance solar cells.
CRIS-Team Scopus Importer:2023-03-20